Impact of Demographic Factors on Retail Investors’ Investment Decisions - An Exploratory Study - Shaikh, Arifur Rehman H.; Kalkundrikar, Anil B. (Indian Journal of Finance, 2011)
An investment is saving of current money and other resources for the future benefit. There are various investment avenues available for retail investors and depending upon ones’ risk appetite, he/she can choose between bank deposits, government / private bonds, shares and stocks, exchange traded funds (ETF), mutual funds, insurance, commodities, currencies, etc. Risk is an important factor to be considered while making an investment in the stock markets. It is the degree of risk taking ability of the investor who has a major impact on his/her investment behaviour and decision making. This paper reveals that demographic factors have an impact on retail investors’ investment decisions. This has been identified on the basis of cross analysis between demographic factors and level of risk taking ability of the investors, and the study was carried out by applying Chi-square test and Correlation analysis.